Hubungan Smartphone Addiction Dengan Kualitas Tidur Pada Remaja di SMK Muhammadiyah 7 Malang - Rosdiana, Yanti; Hastutiningtyas, Wahidyanti Rahayu; Nurul, Nurul (Universitas Tribhuwana Tunggadewi, 2023)
Most smartphone users are teenagers, excessive smartphone use can cause smartphone addiction. Smartphone addiction in teenagers can result in disturbed sleep quality. This study aims to determine the relationship between smartphone addiction and sleep quality in adolescents at SMK Muhamamadiyah 7, Malang Regency. The research design uses analytical observation with a cross sectional approach. The population of this study was 100 students. The inclusion criteria in this study were students aged between 12 and 14 years and were willing to be respondents, while the exclusion criteria in this study were teenagers who were absent or sick while conducting the research. The number of samples obtained in this research was 80 students, samples were taken using purposive sampling technique. The independent variable is smartphone addiction, the dependent variable is sleep quality. The instruments used were a smartphone addiction scale questionnaire sheet and The Pittsburgh Sleep Quality Index (PSQI) questionnaire sheet. Data analysis used the Spearman test. The results of this study show that the majority of respondents have smartphone addiction in the high category (31%). Most respondents had poor sleep quality (61.3%). There is a relationship between smartphone addiction and sleep quality in teenagers at SMK Muhamadiyah 7, Malang Regency (p-value= 0.002). Future research can conduct research on other factors that can influence smartphone addiction and sleep quality.